2001
DOI: 10.1046/j.1462-5822.2001.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of bundle-forming pilus of enteropathogenicEscherichia coliin host cell adherence and in microcolony development

Abstract: SummaryEnteropathogenic Escherichia coli (EPEC) adheres to epithelial cells and forms microcolonies in localized areas. Bundle-forming pili (BFP) are necessary for autoaggregation and the formation of microcolonies. In this study, we show that BFP, expressed by EPEC on epithelial cells, disappeared with the expansion of the microcolony. Bacterial dispersal and the release of BFP from the EPEC aggregates were induced by contact with host cellular membrane extract. In addition, BFP-expressing EPEC adhered direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 26 publications
3
50
2
1
Order By: Relevance
“…Bundle forming pili (BFP) are responsible for promoting the initial attachment of EPEC to epithelial cells (35). EHEC does not express BFP proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Bundle forming pili (BFP) are responsible for promoting the initial attachment of EPEC to epithelial cells (35). EHEC does not express BFP proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The initial studies of Giron et al (1991) demonstrated a significant reduction in localized adherence of EPEC in the presence of BFP antibodies; residual adherence can now be explained by EspA filament and intimin-Tir adherence. Tobe & Sasakawa (2001) implicated BFP in host cell attachment by demonstrating preferential binding of BFP, producing EPEC to the Caco-2 cell surface rather than to existing EPEC microcolonies formed during an earlier infection. These authors also concluded that differential EPEC adherence to cells of different species origin was due to BFP (Tobe & Sasakawa, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also implicated BFP in initial binding of EPEC to host epithelial cells (Donnenberg et al, 1992;Giron et al, 1991;Tobe & Sasakawa, 2001 although other studies which used human intestinal organ culture suggested that BFP were not involved in initial EPEC adherence but only at a later stage to promote microcolony formation (Hicks et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly reported function of T4 pili is adherence to a diverse range of surfaces, from metal, glass, plastics, and rocks to plants and various host tissues (48,51,123,156,164,209,217,313,341,391,393,419,431). T4P have repeatedly been shown to contribute to the infectivity of pathogens-even intracellular pathogens such as Francisella tularensis (344)-firmly establishing them as important virulence factors.…”
Section: Adherence and Aggregationmentioning
confidence: 99%